FOCUS GROUP DISCUSSION PENCEGAHAN HIPERTENSI DAN GIZI LEBIH DENGAN POLA HIDUP SEHAT - Muwakhidah Muwakhidah; Fathiya Nur'aini Azizah; Febri Wulandari; Ayulia Eka Putri; Alvina Damayanti; Valentina Febri Marzaleva; Fathiya Nur’aini Azizah; Saminur Fauzan; Diana Fatmasari; Davinka Aliyya Suprihono; Sadna Izzatul Azka; Niken Diah Haryanti; Fariqa Aisyiyah Alrafi; Tiara Sang Ether; Delia Ismiranti; Yoeristia Roembiasiwi; Sindy Wilujeng (Universitas Muhammadiyah Surakarta, 2026)
Hypertension and nutrition are more health problems that are priorities to be addressed. Complications of hypertension can cause health problems later in life and can cause death. Nutrition is a risk factor for hypertension. For this reason, it is necessary to prevent this problem at the Colomadu Community Health Center. The aim of this activity is to increase the knowledge of posyandu cadres about hypertension and better nutrition so that early prevention can be carried out. The method of activity carried out is by providing outreach and education about preventing overnutrition and hypertension with a healthy lifestyle. This activity was carried out in 2 villages, namely in Bolon Village and Baturan Village, Colomadu District, Karanganyar Regency. This activity was attended by posyandu cadres in the 2 villages. This activity was carried out in conjunction with routine meetings of posyandu cadres in Bolon Village and Baturan Village. In Bol on Village, counseling was carried out on preventing overnutrition with balanced nutrition, which was carried out using the FGD (Focus Group Discussion) method, while in Baturan Village it was carried out in conjunction with a meeting of village posyandu cadres at Siaga Sejahtera Sejahtera (DS3). The cadres were very enthusiastic in participating in the FGD and also asked questions about the material presented. This activity can increase understanding about preventing overnutrition and hypertension. It is hoped that this activity can be passed on to the community in a sustainable manner from cadres to the community.